Ensuring the quality of professional training of future teachers in the context of system approach = Zapewnienie jakości kształcenia zawodowego przyszłych nauczycieli w kontekście podejścia systemowego - Bilyakovska, Olha; Shcherbiak, Iurii; Binytska, Kateryna; Nahorna, Olha (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article examines the professional training of future teachers in the context of ensuring its quality. The process is responsible and complex, and its effectiveness is determined by many factors, including the use of a system approach to organization. During our scientific exploration, we have identified the system approach as a research object and have specifically considered the educational system.
Keywords: system approach; professional training; future teachers; podejście systemowe; kształcenie zawodowe; przyszli nauczyciele